2017
DOI: 10.3892/ol.2017.7347
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic activity of insulin in the development of non‑small cell lung carcinoma

Abstract: Abstract. Insulin is associated with the progression of numerous different types of cancer. However, the association between insulin and non-small cell lung carcinoma (NSCLC) remains unknown. The aim of the present study was to evaluate the role of insulin in the proliferation, migration and drug resistance of NSCLC cells, and to determine whether the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) pathway was involved. NSCLC cells were treated with insulin in the absence or presence of LY294002, an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Is it possible that IR-A or IGF1R activation may have deleterious consequences because it triggers proliferation? On the one hand, there is some data about these receptors being involved in carcinogenesis, so strategies for treating some tumors based on inhibition of IGF1R and IR-A are being developed [ 299 , 301 , 302 , 303 ]. On the other hand, promising medications for treating various diseases were designed based on IGF-1 (another IGF1R ligand) and these substances are already under evaluation in clinical studies [ 304 , 305 , 306 ].…”
Section: Discussionmentioning
confidence: 99%
“…Is it possible that IR-A or IGF1R activation may have deleterious consequences because it triggers proliferation? On the one hand, there is some data about these receptors being involved in carcinogenesis, so strategies for treating some tumors based on inhibition of IGF1R and IR-A are being developed [ 299 , 301 , 302 , 303 ]. On the other hand, promising medications for treating various diseases were designed based on IGF-1 (another IGF1R ligand) and these substances are already under evaluation in clinical studies [ 304 , 305 , 306 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some basic research provides possible explanations. An in vitro study using non-small-cell lung cancer cells suggested that insulin promotes the proliferation, migration, and invasion of lung cancer by increasing the phosphorylation of IR substrate 1 and activating the phosphoinositide 3-kinase/protein kinase B pathway (12). Another study showed that ablation of IR substrates 1 and 2 suppressed Kras -driven lung tumorigenesis (13).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that insulin can up-regulate the expression of MMP3 genes in NSCLC cells, but its expression will be affected by PI3K/Akt. Inhibited by pathway inhibitors (29).…”
Section: Current Status Of Lusc Treatment Targets and Mmp3mentioning
confidence: 99%